Análise crítica multimodal da comodificação de homens e mulheres em capas de CDs funk - Oliveira, Edinéia Aparecida Chaves de (2013)
In this study, based on ACD and from metafunctions of language of Grammar of Visual Design by Kress and van Leeuwen (1996, 2001), I analyze multimodal commodification of women and men in forty funk 2012 CD covers. I hypothesized that men and women are asymmetrically commodified, so that (i) men are represented as subjects and women as objects in these promotional texts, and (ii) these differences are evidence of marked social representations for men and women in the funk movement. The findings suggest that funk promotion essentially commodifies images of people (38 covers). In these examples, men are represented as Masters of Ceremonies (MCs), Disk Jockeys (DJs) or singers in images that (i) highlight their professional and artistic protagonist role in dances, and (ii) present some of their objects of desire, including cars, jewelry and women. Women are represented as dancers, or sexily pose for the interactive male participant to invite him to enjoy of the music or even seduce him (fetish body). These results support the hypothesis that men are subject of the movement, and women are part of the list of theirs objects of desire and power. The images project a social representation of a male consumer who wants to have the same success of the protagonists and the same objects of desire, including women. This demarked division of social roles in the representations of funk CD covers, by hypothesis, must be a consequence of the larger context of the dances, the music and the movement itself. It is reasonable to assume, therefore, that these representations are clues of sexist positions that favor men over women in a larger culture structure that controls these practices and discourses.